Synthesis of novel Cu2S nanohusks as high performance counter electrode for CdS/CdSe sensitized solar cell - Kamaja, Chaitanya Krishna; Devarapalli, Rami Reddy; Dave, Yasha; Debgupta, Joyashish; Shelke, Manjusha V. (Journal of Power Sources, 2016)
An important component of quantum dot sensitized solar cells (QDSSC) is the counter electrode which mediates the regeneration of oxidized quantum dots by reducing the polysulphide electrolyte. However, design and synthesis of an efficient counter electrode material is a challenging task. Herein, we report the synthesis of a unique Cu2S nanohusks directly on FTO coated glass substrates by electrodeposition and used as a counter electrode in QDSSC. When these electrodes are used for the reduction of polysulfide electrolyte in QDSSC, they exhibit higher catalytic activity and photovoltaic performance as compared to the Platinum counter electrode. The power conversion efficiency of about 4.68% has been achieved by optimizing the deposition time of Cu2S. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: counter electrode; Cu2S electrodeposition; Cu2S nanohusks; Quantum dot-sensitized solar cell